2017
DOI: 10.21037/acs.2017.05.11
|View full text |Cite
|
Sign up to set email alerts
|

Septal myectomy after failed septal alcohol ablation

Abstract: Despite septal myectomy remaining the gold standard septal reduction therapy for hypertrophic obstructive cardiomyopathy (HOCM), there has been a disproportionate use of alcohol septal ablation (ASA) worldwide.Absolute resolution of left ventricular outflow tract (LVOT) obstruction with ASA is not achieved in a substantial proportion of patients. The mechanisms of failure from ASA are partially understood and described. Residual obstruction in hypertrophic cardiomyopathy is associated with worse clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…Some researchers believe that the alleviation of LVOT obstruction is achieved by the change in the left ventricular contraction sequence caused by conduction damage (17). In addition, the present study revealed that the risk of AVB after SSM alone is low, but concomitant preoperative RBBB increases the risk of AVB after surgery (13,18), and postoperative PPM affects long-term survival (13). Previous reports of ASA for the treatment of OHCM showed that ASA is associated with right bundle branch injury (19), with an incidence rate as high as 58% (8,20,21).…”
Section: Discussionsupporting
confidence: 49%
“…Some researchers believe that the alleviation of LVOT obstruction is achieved by the change in the left ventricular contraction sequence caused by conduction damage (17). In addition, the present study revealed that the risk of AVB after SSM alone is low, but concomitant preoperative RBBB increases the risk of AVB after surgery (13,18), and postoperative PPM affects long-term survival (13). Previous reports of ASA for the treatment of OHCM showed that ASA is associated with right bundle branch injury (19), with an incidence rate as high as 58% (8,20,21).…”
Section: Discussionsupporting
confidence: 49%
“…In this series, surgical myectomy rather than repeat ASA appeared to be the favored intervention for residual outflow tract obstruction after unsuccessful ASA; however, operation in this setting can be problematic. 29,30 In a review of 31 patients who underwent septal myectomy after failed alcohol ablation, Quintana and coauthors 31 noted a higher risk of postoperative complete heart block in patients who had prior ASA compared with a control group of patients who had myectomy without a history of ASA (19.4% vs 1.6%). The increased risk of heart block observed with septal myectomy after ASA may be explained by the differential effects of each procedure on the conduction system.…”
Section: Septal Myectomy After Unsuccessful Ablationmentioning
confidence: 99%
“…Additionally, the few CMR images available in the present study revealed that the underlying mechanism of previously failed ASA might be attributed to variable extent and uncontrollable location of infarcted myocardium induced by ASA. This finding was consistent with the study by Valeti et al Several mechanisms have been proposed to address the failure of ASA in some HOCM patient population . Unlike the surgical septal myectomy which provides precise and discrete resection, ASA induces myocardial infarction of hypertrophic basal septum through perforator artery.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with the study by Valeti et al 18 Several mechanisms have been proposed to address the failure of ASA in some HOCM patient population. 14,19 Unlike the surgical septal myectomy which provides precise and discrete resection, ASA induces myocardial infarction of hypertrophic basal septum through perforator artery. The effects are limited by anatomical morphology, perforator artery distribution, and collateralization.…”
Section: Discussionmentioning
confidence: 99%